Legal Protection For Construction Service Providers in Cases of Building Failure - Anrizal, Anrizal; Sami'an, Sami'an; Hardjomuljadi, Sarwono (PT. Multidisciplinary Press Indonesia, 2025)
Building failure is a condition of collapse or non-functioning of a building when the final handover of construction services is carried out where this is caused by negligence on the part of the Service Provider, so that they are obliged to be responsible for the failure that exists. The problems in this study include 1) How to implement legal protection for construction service providers in cases of building failure. 2) What are the weaknesses in implementing legal protection for construction service providers in cases of building failure so that they are not yet fair. 3) How to reconstruct legal protection for construction service providers in cases of building failure based on the value of justice. The approach method used is empirical juridical. In this study, the theory used is the Pancasila Justice Theory. The results of the study found that the implementation of legal protection for construction service providers, especially related to building failure problems, has not been based on the principle of justice because building failure problems should be resolved through civil law and administrative sanctions, not criminal action. And related to various weaknesses in the implementation of legal protection are still found, where this is caused by the weakness of existing legal regulations, law enforcement structures and community culture.